Sexualidade e planejamento reprodutivo dos adolescentes vivendo com HIV/Aids: um desafio ao cuidado em saúde - Braga, Alexandre Lelis [UNIFESP] (2017)
Adolescents infected with the human immunodeficiency virus (HIV) by vertical transmission present particularities related to their sexuality. Despite their maturity, they are forced to overcome challenging obstacles such as dealing with a sexually transmitted disease fraught with stigmatizing attributes, in addition to living with the fear of rejection of their partners due to the disclosure of their seropositivity. This work is a literature review whose objective was to identify publications about sexuality and reproductive rights in adolescents living with HIV / AIDS from 2005 to 2015. The results show that adolescents either date or wish to date and want to have children. Meanwhile, there is evidence of limited knowledge about prophylactic measures to avoid infecting the fetus and the serodiscordant partner. They have less ability to negotiate condom use, thus avoiding a love relationship or postponing sexual life for fear that insistence on the use of condoms may lead to a diagnostic disclosure. These findings corroborate the need for public policies primarily focused on diagnostic disclosure and reproductive planning. It is important to emphasize that the adolescent has the right to decide whether to have children, when to have them and the timing between the gestations, entrusting the professional to guarantee access to all the necessary information for a conscious and responsible decision. The findings show that it is of paramount importance to prioritize this group's access to reproductive health.